Política, imprensa local, perseguição: o Golpe de 1964 no Pontal do Triângulo Mineiro - Ferreira, Caio Vinicius de Carvalho (2017)
In 1964, a coup d'état occurred in Brazil, in which the armed forces, together with a portion of the population, took political posts and established an authoritarian government. In the state of Minas Gerais, in the micro-region of Pontal do Triângulo Mineiro, in the city of Ituiutaba, far from the capitals, the civil-military coup was felt in the form of intervention. The arrival of an armed military junta in cooperation with civilians in the city forced the resignation of the mayor, the vice mayor and five other councilors, as well as the arrestments of three of the latter and an mayor advisor - all linked to labor policies, mostly affiliated to the PTB (Brazilian Labor Party). They were replaced by another political group, linked to the UDN (National Democratic Union) local directory. This junta also closed a local newspaper, Folha de Ituiutaba, and prevented its circulation, culminating in the arrestments of the owner and his chief editor, who were taken to the Political Order Department (DOPS) in Belo Horizonte and forced to testify. In this context, a newspaper that has already circulated in the region, the Correio do Triângulo, reappears, which, in this new version, returns as a spokesman for this new group that has won local political hegemony. This alliance still persecuted and arrested local union leaders, dismantling the newly founded Union of Rural Workers of Ituiutaba. This research proposes to analyze the consequences of the civil-military coup in the micro-region of Pontal do Triângulo Mineiro, thinking beyond traditional studies on the coup that prioritize reviews in large capitals and national levels. We seek to understand the historical process, factors and repercussions, actions and reactions to these events and the way they were felt, experienced and executed in the local context. In this way, we investigate the political plot when the coup was established and its impact on the micro-region. In order to do so, it is intended to work with different sources available, intersecting information and criticizing several documents, such as: hemerographic sources, textual sources - city hall minutes, DOPS documents of Belo Horizonte, personal document - and oral sources - testimonials and narratives of subjects who experienced these events, directly or indirectly, in the micro-region, in the year that the implementation of the dictatorship and the local takeover took place.